The edge of the Kuiper belt: the Planet X scenario - Melita, Mario Daniel (2004)
Our goal is to determine whether or not the observed sudden termination of the Edgeworth–Kuiper belt can be the result of perturbations from a hypothetical planet. We investigate the effects that such an object would produce on the primordial orbital distribution if the transneptunian objects, for a range of masses and orbital parameters of the hypothetical planet. In this numerical investigation, the motion of the hypothetical planet was influenced by the existing planets but not by its interaction with the disk. We find that no set of parameters produce results that match the observed data. Dynamical interaction with the disk is likely to be important so that the orbit of the hypothetical planet changes significantly during the integration interval. This is also discussed. The overall conclusion is that none of the models for the hypothetical planet that were investigated can reproduce the observed features of the Edgeworth–Kuiper belt starting from any probable primordial distribution.